ENERGY VALUE IN BIOMASS AND PLASTIC COMPONENTS OF MUNICIPAL SOLID WASTE - Nidhi, Chaitanya; Sharma, Bhoora; Singh, Prabhat (MATTER: International Journal of Science and Technology, 2017)
Burning potencies of constituents of municipal solid waste (MSW) indicate energy value stored in them. A significant portion of biodegradable as well as non-biodegradable waste is still80 not recycled and most of them are either burnt or dumped in the landfills. The scope of this work is to study the energy value of selected biomass (dry garden leaves) and two plastic materials, low density polyethylene (LDPE) and polystyrene (PS), collected from an educational campus in Varanasi, India. Cow dung which is still used as domestic fuel in dry cake form in many parts of the country, has also been included. Two pellet batches of biomass, one each of Ashoka (Saraca Asoca) tree leaves and Cow dung, two pellet batches of plastic, one each of low density polyethylene (LDPE) and polystyrene (PS); and twelve biomass-plastic blended pellets have been prepared and tested. Proximate analyses and higher heating values (HHVs) were measured and compared with the gross calorific values (GCVs) of various grades of Indian non-coking thermal coals. The results indicate that on blending of biomass materials with plastics in 1:1 ratio, the HHV of mix exceed GCV of grade A non-coking coal. A 2:1 ratio gives material with heating values higher than grade C coal. Other tested mix proportions also produced heating values exceeding D grade coal. Thus, it appears feasible to produce secondary fuel using components of MSW for domestic consumptions. This is a non-conventional and renewable source of energy. This may partly reduce the dependence on fossil fuel (like coal) and provide an alternate reuse pathway for such materials.